Histological modification in TRAM flap in rats treated with pentoxifylline - Lucca, Audrien Furlan de (2014)
PURPOSE: To investigate the blood vessels' concentration in TRAM flap's rat model, in the presence of pentoxifylline.METHODS:32 male, Wistar-EPM rats were divided into two groups. Control group (C): 0.5 ml of saline, intraperitoneally, once a day, for seven days before flap elevation; PTX group (P): pentoxifylline (20mg/kg/day), intraperitoneally, for seven days before flap elevation. After that, they were submitted to a caudal unipedicle TRAM flap. On the fifth postoperative day, percentages of flap necrosis were determined via the paper template method and Tram flap's zone IV skin biopsies were taken for histological analysis.RESULTS:the mean percentage of flap necrosis in group C was 58.7 % and in group P, 31.1 (Wilcoxon test; p = 0.003). Mean capillary vessels number in zone IV's skin in C group was 33.4 and in P group was 71.9 (p=0.008).CONCLUSIONS: Pentoxifylline was effective reducing the necrosis in the caudal unipedicle TRAM flap in the rat as well as increasing the number of capillaries in an ischemic zone (zone IV).